A comprehensive framework for District Energy systems upgrade. (October 2021) - Ferrari, Luca; Morgione, Stefano; Rutz, Dominik; Mergner, Rita; Doračić, Borna; Hummelshøj, Reto M.; Grimm, Sebastian; Kazagic, Anes; Merzic, Ajla; Krasatsenka, Aksana; Rossi, Simone; Pauschinger, Thomas; et al.
Abstract: District Heating Systems have a great role to play in achieving increasingly challenging EU and global climate goals, thus improving performance and further development of existing large and small systems across Europe, often far from state-of-the-art standards, they represent an opportunity not to be missed. The paper outlines the key findings of the H2020 project UpgradeDH, formed by a very heterogeneous Consortium involving partners from all over Europe and different sectors of the District Heating (DH) supply chain, aiming to demonstrate the impacts of best practices on various DH systems and proposing a systemic approach to DH upgrading, that may be easily adopted and scaled up across Europe and beyond. Key challenges regarding energy generation, distribution and consumption are tackled, sharing knowledge amongst all partners and the general audience, and suitable practical solutions applied to improve DH systems' performances. Integration of renewable sources, promotion of sector coupling through storages and advanced digital tools, pumping and other operational optimization approaches are being applied in a variety of contexts, achieving multi-energy integration, full exploitation of existing assets and reduction of energy losses, operative costs and GHG emissions. Sound technical and business approaches are integrated by developing new business models and regional action plans designed to ensure overall sustainability and increase opportunities for technological scaleup and deployment of modern DH systems. UpgradeDH represents, in summary, an easily accessible resource to inform, inspire and support the development roadmap of existing DH systems, that are facing the modernization and decarbonization challenge.